Issues with the use of medicines in paediatrics: Off-label and unlicensed use, and formulation uncertainty - Czarniak, Petra (Curtin University, 2014)
Prescribing of drugs for children is not always in accordance with their registration specifications or they may even be unlicensed which can give rise to serious adverse events. This study has found that approximately 30% of drugs prescribed in a major teaching hospital for children did not conform to the registration specifications. It has also proposed methods to improve evidenced-based prescribing in children. In addition it has provided enhanced scientific information for the prescribing of lincomycin infusions.